A New Magnetic Coupling Mechanism for Patrol Robot Wireless Charging System. (October 2020) - Xue, Tiange; Meng, Xiangzhong; Hou, Liyang
Abstract: In this paper, a new magnetic coupling mechanism with Double-Layer-Double-D (DLDD) coil and nanocrystalline magnetic core is proposed for patrol robot wireless charging system. In comparison with the traditional magnetic coupling mechanism, the magnetic coupling mechanism proposed in this paper has higher magnetic induction intensity, lower magnetic leakage, higher coupling coefficient and better anti-offset ability. Hence, the efficiency of the wireless charging system can be improved. The organization of this paper is as follows. Firstly, the topological structure of the coil and magnetic core of the new magnetic coupling mechanism are introduced. Then, based on the working principle of the wireless charging system, the influence of the new magnetic coupling mechanism parameters on the transmitted power and efficiency of the wireless charging system is analysed. Moreover, in comparison with the conventional magnetic coupling mechanism, the electromagnetic properties of the two kinds of magnetic coupling mechanism are analysed and compared, including magnetic induction intensity, coupling coefficient and anti-offset ability, etc.